Envisioning nature-positive futures for Europe: inspiring transformative change at the biodiversity nexus - Lazurko, Anita; de Pater, Mara; Kim, HyeJin; Hebinck, Aniek; Biesbroek, Robbert; Declerck, Fabrice; Krupnik, Seweryn; Okruszko, Tomasz; Pereira, Laura M.; Proka, Antonia; Sakellari, Eirini; Harrison, Paula A. (Taylor & Francis, 2025)
Transformative change is required to secure a liveable future for people and nature. The Nature Futures Framework (NFF) is a heuristic tool for supporting the creation of plural visions of nature-positive futures that build shared motivation for transformative change. Integrating nexus approaches with the NFF highlights the foundational role of biodiversity in supporting desirable outcomes across sectors (i.e. the biodiversity nexus). We bring these areas of biodiversity research together to ask: what could plural nature-positive futures for Europe in 2050 look like that explicitly leverage synergies in the biodiversity nexus? To address this, we co-created nature futures for Europe with 26 participants representing diverse sectors and regions, resulting in three visions underpinned by different value perspectives: Dòigh Nàdair: The way of nature (Nature as Culture), NaturAll (Nature for Nature) and Return to Nature (Nature for Society). Subsequent analyses and a follow-up webinar enriched the visions, identifying opportunities for more synergistic nexus interactions. Our findings highlight how plural visioning processes can generate distinct visions with positive nexus synergies enabled by unique indirect drivers (e.g. biodiversity-food synergies enabled by re-ruralisation and spiritual human-nature connections in ‘Dòigh Nàdair’, technological advancements in ‘Return to Nature’ and mimicking natural ecological processes in ‘NaturAll’). Yet, the visions also share common features (e.g. restored ecosystems and participatory governance) underpinned by overlapping value perspectives. We demonstrate how explicit consideration of the biodiversity nexus in visioning processes can reveal opportunities to align biodiversity goals with broader sectoral priorities, thereby helping sustain ambitious biodiversity outcomes amid diverse and competing agendas.